Neurorescue Effects of Frondoside A and Ginsenoside Rg3 in C. elegans Model of Parkinsons Disease - Pawanrat Chalorak; Tanatcha Sanguanphun; Tanapol Limboonreung; Krai Meemon (My University, 2021)
Parkinson’s disease (PD) is a currently incurable neurodegenerative disorder characterized by the loss of dopaminergic (DAergic) neurons in the substantia nigra pars compacta and α-synuclein aggregation. Accumulated evidence indicates that the saponins, especially from ginseng, have neuroprotective effects against neurodegenerative disorders. Interestingly, saponin can also be found in marine organisms such as the sea cucumber, but little is known about its effect in neurodegenerative disease, including PD. In this study, we investigated the anti-Parkinson effects of frondoside A (FA) from Cucumaria frondosa and ginsenoside Rg3 (Rg3) from Panax notoginseng in C. elegans PD model. Both saponins were tested for toxicity and optimal concentration by food clearance assay and used to treat 6-OHDA-induced BZ555 and transgenic α-synuclein NL5901 strains in C. elegans. Treatment with FA and Rg3 significantly attenuated DAergic neurodegeneration induced by 6-OHDA in BZ555 strain, improved basal slowing rate, and prolonged lifespan in the 6-OHDA-induced wild-type strain with downregulation of the apoptosis mediators, egl-1 and ced-3, and upregulation of sod-3 and cat-2. Interestingly, only FA reduced α-synuclein aggregation, rescued lifespan in NL5901, and upregulated the protein degradation regulators, including ubh-4, hsf-1, hsp-16.1 and hsp-16.2. This study indicates that both FA and Rg3 possess beneficial effects in rescuing DAergic neurodegeneration in the 6-OHDA-induced C. elegans model through suppressing apoptosis mediators and stimulating antioxidant enzymes. In addition, FA could attenuate α-synuclein aggregation through the protein degradation process.
Keywords: Pars compacta; Seaweed-derived Bioactive Compounds